The characteristics of mcr-bearing plasmids in clinical Salmonella enterica in Sichuan, China, 2014 to 2017 - Sun, Xinran; Zhang, Lin; Meng, Jiantong; Peng, Kai; Huang, Weifeng; Lei, Gaopeng; Wang, Zhiqiang; Li, Ruichao; Yang, Xiaorong (Frontiers in Cellular and Infection Microbiology, 2023)
Salmonella is one of the most important zoonotic pathogens and a major cause of foodborne illnesses, posing a serious global public health hazard. The emergence of plasmid-mediated mcr genes in Salmonella has greatly reduced the clinical choice of salmonellosis treatment. The aim of this study was to investigate the plasmid characteristics of mcr-positive Salmonella identified from patients in Sichuan, China during 2014 to 2017 by whole genomes sequencing. In this study, a total of 12 mcr-positive isolates (1.15%, ; mcr-1, n=10; mcr-3, n=2) were identified from 1046 Salmonella isolates using PCR. Further characterization of these isolates was performed through antimicrobial susceptibility testing, conjugation assays, whole genome sequencing, and bioinformatics analysis. The mcr-1 gene in these isolates were carried by three types of typical mcr-1-bearing plasmids widely distributed in Enterobacteriaceae (IncX4, IncI2 and IncHI2). Of note, two mcr-1-harboring IncHI2 plasmids were integrated into chromosomes by insertion sequences. Two mcr-3-bearing plasmids were IncC and IncFIB broad-host-range plasmids respectively. Genetic context analysis found that mcr-1 was mainly located in Tn6330 or truncated Tn6300, and mcr-3 shared a common genetic structure tnpA-mcr-3-dgkA-ISKpn40. Overall, we found that mcr gene in clinical Salmonella were commonly carried by broad-host plasmids and have potential to transfer into other bacteria by these plasmids. Continuous surveillance of MDR Salmonella in humans and investigation the underlying transmission mechanisms of ARGs are vital to curb the current severe AMR concern.